If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(7-3x)+1=2x-1
We simplify the equation to the form, which is simple to understand
2(7-3x)+1=2x-1
Reorder the terms in parentheses
+(+14-6x)+1=2x-1
Remove unnecessary parentheses
+14-6x+1=+2x-1
We move all terms containing x to the left and all other terms to the right.
-6x-2x=-1-14-1
We simplify left and right side of the equation.
-8x=-16
We divide both sides of the equation by -8 to get x.
x=2
| (3x+4)(x-3)=10 | | 8+-176=-72 | | 567=-6(10x-16) | | 8+176=-72 | | (x-8)*(x-8)-18=-2 | | 4k-7=2+k | | 504=-16x^2+484 | | 2(g-2)-4=3(g-3) | | 209-3x=33x+21 | | 75-6x=12x+15 | | 3+5d=11+4d | | 6x-7=3x-11 | | 9(2x+14)-4(3x+17)=64 | | -3x+6=18 | | 3x^2-27x=-2x^2-9x-16 | | 5.50+4.00(486-a)=2416 | | -486=6(7x-11) | | 7-8x=47-22x | | 3x-5=5x+12 | | 4(5y-4)=12y | | -61*3=x | | -120=-4(7x+9) | | 5y-9=7y-13 | | 4x+6=4x+6 | | 3x=5+2(3+4) | | 2x+3x=2x+40 | | 3x+(x-8)=12 | | 7y=6(y+10) | | x+x+2+3x=57 | | [x-5]=-9 | | -(4y+3z-2)= | | [x-5]=9 |